Pengaruh Model Pembelajaran dan Minat Belajar Terhadap Hasil Belajar Permainan Rounders Pada Siswa Sekolah Dasar - Nugroho, Wasis; Sinulingga, Albadi; Simatupang, Nurhayati (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine the difference in the influence of the teaching games tournament learning model and teaching games for understanding on the learning outcomes of the rounders game, the difference in the influence of high interest and low interest on the learning outcomes of the rounders game; and the interaction between the learning model and interest in the learning outcomes of the rounders game in elementary school students. This research method is an experiment with a 2 x 2 factorial design. The population is 56 students from SDN 132413 and SDN 132404 Tanjung Balai. The sample consisted of 32 students consisting of 4 groups, there were 8 in each group based on the top and bottom 27%. Data collection uses pretest and posttest. The instrument in this research is a questionnaire. The data analysis technique used was analysis of variance (two-way ANOVA) at a significance level of α = 0.05. The results of this research show that: there is a significant difference in the influence of learning models and teaching games tournaments and teaching games for understanding on the learning outcomes of the rounders game; There is a significant difference in the influence of high interest and low interest on the learning outcomes of the rounders game; and there is an interaction between the learning model and interest in the learning outcomes of the rounders game in elementary school students. Conclusion, There is a significant interaction between the teaching games tournament learning model and teaching games for understanding and interest (high and low) on increasing learning outcomes for the game of rounders. Keywords: teaching games tournament, teaching games for understanding, interests, results of learning the rounders games